KOMPUTASI GRID MENGGUNAKAN GLOBUS UNTUK MENGHITUNG OPSI PUT AMERIKA DENGAN SIMULASI MONTE CARLO - , AJI PURWINARKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Internet computing and Grid technologies change the way we tackle complex problems. Grid computing continues to hold promise for the high-availability of a wide range of computational systems and techniques. Distributing an application on several machines is one of the key aspects of Grid computing. Globus Toolkit is a provider of Grid computing libraries. Grid computing can be used to run applications with the American put option using Monte Carlo simulation. A Monte Carlo simu- lation is used to forecast the stock price. The results of research conducted showing that more simulations are performed, it will give accurate value of the stock price. The results of this study indicate that a growing number of simulations carried out, would result in the value of the put option that converges with a small standard error and computational processes by using a large number of processors will be faster